Application of Electrolyzed oxidized (EO) water in biodecontamination of Packaging Materials used in Dairy and Food Industry - Hati, Subrota; Patel, Maulik; Prajapati, JB (Indian Journal of Dairy Science, 2018)
EO water is non-toxic, non-irritant, environmentally and ecologically safe. In the study, EO water is used to evaluate the antimicrobial activity against test organisms and showed highest antimicrobial activity against P. aeruginosa, S. aureus, Bacillus subtilis and E. coli. The tolerance power of B. cereus, E. coli, S. typhi and Listeria monocytogenes against oxidized water was evaluated and none of the organisms survived against oxidized water exposed for different time intervals. The results suggested that packaging materials. i.e. Low Density Polyethylele (LDPE) film for liquid milk packing (Capacity: 500/1000 ml), Polystyrene Cups for ice cream and dahi/ yoghurt packing exposed with EO water for 5 min showed lethal effects on microbes compared to 2 minutes exposure. In another experiment, uncleaned petri plates were also treated with oxidized water and observed that none of the bacterial cells were survived in the uncleaned plates after the treatment.